3D Printing Technology: A Contemporary Revolution in Drug Development - Katiyar, Arpit (Asian Journal of Pharmaceutics (AJP), 2023)
As a recently developing technology, three-dimensional (3D) printing has a lot of potential in the pharmaceutical sector and can cater patients and the pharmaceutical industry with innovative approaches. This technology allows for the accurate creation of dosage forms, which can help with drug product design. It also facilitates treatment for patients, such as individualized dosing, which can be used to treat particular disease states or patient groups. New approaches and techniques for creating unique medication delivery systems are made possible by the evolution of 3D techniques. The use of 3D printing technologies in the pharmaceutical industry is outlined in this paper, with special consideration devoted to the benefits of these technologies for attaining quick medication delivery, personalized drug delivery, compound drug delivery, and customizable drug delivery. This article also demonstrates the history, advantages, prospects, applications, constraints, and difficulties of 3D printing techniques in the area of developing pharmaceutical formulations. Pharmaceutical manufacturing is only one of many industries where the 3D printing (3DP) technique has had an important impact since its introduction in the early 1980s. Researchers and the public are becoming more interested in creating customized or individualized dosage forms as a result of the shifting horizons. The current work validates the viability of volumetric 3DP for quickly printing pharmaceutical items. This novel technology can enable the quick, on-demand manufacture of pharmaceuticals and medical equipment with further optimization.